Improvement and Change Process at a Venezuelan School - Luis A. Colmenares Gilly (Universidad Autónoma de Madrid, 2016)
This article presents a study case of an improvement process at a Venezuelan school. Intended to identify and describe the policies and measures placed in practice and to analyze the effects and consequences of the mentioned while looking to identify the existing relation between the policies, the measures and the changes perceived by the teaching community.